Anacardiaceae endémicas del Perú - Leon, Blanca (2006)
The Anacardiaceae are represented in Peru by 13 genera and 40 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), basically trees and shrubs. Here we recognize seven endemic species in three genera. This family includes one endemic genus, Orthopterygium. Endemic taxa are found mainly in Desert Shrubland, Mesoandean, and Very Humid Montane and Humid Lowland Amazonian Forests regions, between 125 and 2400 m elevation. No endemic Anacardiaceae have been registered to date within Peru’s protected areas system.